Phase‐selective Route to V‐O Film Formation: A Systematic MOCVD Study Into the Effects of Deposition Temperature on Structure and Morphology1 . Issue 10 (23rd November 2015) - Spanò, Simon F.; Toro, Roberta G.; Condorelli, Guglielmo G.; Messina, Grazia M. L.; Marletta, Giovanni; Malandrino, Graziella
Abstract : A systematic study into the MOCVD of V‐O films using the vanadyl‐acetylacetonate [VO(acac)2 ] precursor is carried out. The films are prepared via low pressure MOCVD on Si(001) substrates. The nature and quality of films are examined by varying operational parameters, e.g., deposition temperature, precursor vaporization rate, and flow of oxygen reacting gas. X‐ray diffraction data point to the formation of crystalline films in the range 200−550 °C. Outside of this temperature ranges amorphous phases were obtained. Field‐emission scanning electron microscope (FESEM) images indicate very homogeneous surfaces with grain shape and dimensions depending on operational conditions. Energy dispersive X‐ray (EDX) and X‐ray photoelectron spectroscopy (XPS) analyses point to the absence of any C contamination. Abstract : A systematic study is carried out into the MOCVD of V‐O films using the vanadyl‐acetylacetonate precursor on a Si(001) substrate. XRD data point to the formation of crystalline films in the range 200–550 °C, with different phases forming within the investigated range.